Implementation of Halaqah and Recitation Methods in Tahfidz Al-Quran in Integrated Islamic Elementary Schools (Universitas Muhammadiyah Sidoarjo, 2015)
This research has the purpose to explain Tahfidz al-Quran with the method halaqah and recitation in SDIT EL-HAQ Banjarsari Buduran Sidoarjo. Primary schools have a curriculum Office as usual, but typically have superior memorize the al-Quran chapters 30 and 29. So that schools implement the curriculum Tahfidz 1 hour lesson / 60 min ute the implementation, each morning. Then its implementation tahfdiz al-Quran, schools have determine halaqah-halaqah in accordance with rote ability learners. With the aim of formation halaqah held so much potential students can be accommodated in each halaqah. In addition in the amount of the halaqah slightly so management learning easier. While the method can strengthen the rote recitation of learners,whenI got hometheyrepeat memory. So rote learners getting stronger. Although there are some obstacles while implementing methods halaqah and recitation, the teacher has a solution which varies according to the level of understanding of learners.